(untitled) (Contemporary Journal of Social Science Review, 2025)
Empowering women improves broader human, social,and economic outcomes. The sustainability of agriculture can empower rural households, and women constitute nearly half of Pakistan’s population. This study adopted a descriptive school student writing improvement design. It was selected because it enabled the researcher to collect and analyze data without manipulating any variables in the field. Study was conduct in Region D.G Khan (Southern Punjab). There were 80 women in each of the four districts that made up the target population for the proposed study. A simple random sampling technique was used to select 320 respondents. In order to collect data from women, the researcher developed an adapted questionnaire. Analyzing processors requires converting human responses into numbers. The data were analyzed using SPSS (Statistic Package for Social Sciences). An important ceremonial focus on human rights and sustainable development is empowerment. The persistent patriarchal culture in the Southern Punjab region D.G Khan hampers women’s participation in the workforce. Women have inherited much wealth from their families, but most of it has gone to men. To keep Pakistan’s economy growing, women empowerment is crucial.